Sustainability Of Muslim Family Livelihoods In The Perspective Of Sustainable Development Goals - Ahmad Alamuddin Yasin; Adang Djumhur Salikin; Aan Jaelani; Edy Setyawan (CV. AFDIFAL MAJU BERKAH, 2023)
According to the classical scholarly view that health, education, and others of a primary nature other than clothing, feed, boards are not the responsibility of the husband in the corridors of living. The problem that often occurs is not only primary needs, wives also often demand hal-things that are secondary. A shift in understanding of the concept of living needs to be developed. The purpose of this study is to evaluate the sustainability of livelihoods in this age of fashionrn. This research uses a multiple case study approach. Data sources obtained through 2 sources. The results showed that living in today's era does not only revolve around food, clothing and shelter. rather, the meaning of living today shows the meaning of the cost of life in the form of primary, secondary or tertiary. The sustainability of the meaning of living shows conformity with the SDGs program which is summarized in 3 aspects, namely: welfare aspects, environmental aspects and equality aspects.